1995
DOI: 10.1002/jcp.1041640208
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in phosphorylation of the transcription factor CREB in the embryonic murine palate

Abstract: Cyclic AMP, via activation of cAMP-dependent protein kinase (PKA) and subsequent protein phosphorylation, regulates a number of cellular and tissue responses that are critical to normal development of the mammalian palate. The present study examines the expression, distribution, and phosphorylation in the developing murine palate of a substrate for PKA known as the cAMP-response element binding protein (CREB). This 43 x 10(3) M(r) protein functions as a regulator of cAMP-inducible gene expression. CREB is expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…26 The expression of CREB occurs at constant levels throughout the palatal development.26'27 Its predominant nuclear localization and a developmental increase in the phosphorylated form of CREB in palatal cells indicates that CREB-mediated gene transcription is likely regulated by changes in its phosphorylation rather than by changes in its expression.26 Results from our laboratory showed that the ontogeny of not only CREB but also several isoforms of CREM (activating and repressing) remained unchanged in the developing palate. Expression of ATF-1 and ATF-2, however, gradually decreased with the progression of development.27'28 Nuclear extracts of developing palate tissue contain CREB, CREM and an unidentified TF other than ATF-128 that bind to CRE forming a single protein-DNA complex.…”
mentioning
confidence: 94%
“…26 The expression of CREB occurs at constant levels throughout the palatal development.26'27 Its predominant nuclear localization and a developmental increase in the phosphorylated form of CREB in palatal cells indicates that CREB-mediated gene transcription is likely regulated by changes in its phosphorylation rather than by changes in its expression.26 Results from our laboratory showed that the ontogeny of not only CREB but also several isoforms of CREM (activating and repressing) remained unchanged in the developing palate. Expression of ATF-1 and ATF-2, however, gradually decreased with the progression of development.27'28 Nuclear extracts of developing palate tissue contain CREB, CREM and an unidentified TF other than ATF-128 that bind to CRE forming a single protein-DNA complex.…”
mentioning
confidence: 94%
“…One very common birth defect is cleft palate, which occurs in 1:500 to 1:1000 live births (9). PKA activation and regulation have been previously described to play important roles in cAMP response element-binding protein (CREB) phosphorylation during palate formation (10). However, its function in relation to the CNC has not been elucidated.…”
mentioning
confidence: 99%
“…The CREBBP-mediated transcription is likely regulated by changes in its phosphorylation rather than by changes in its expression. 32 Meanwhile, expression of ADCY9 was upregulated in the dental pulp stem cultures of NSCL/P patients. 21 Therefore, rs8049367 might contribute to DD and NSCL/P through its pleiotropic effects on CREBBP and ADCY9 , respectively.…”
Section: Discussionmentioning
confidence: 99%